2020
DOI: 10.3390/toxins12060350
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zearalenone on the Cytokine Environment, Oxidoreductive Balance and Metabolism in Porcine Ileal Peyer’s Patches

Abstract: The aim of the present study was to determine the effect of zearalenone (ZEN), administered per os to gilts at doses equivalent to 50%, 100%, and 150% of no-observed-adverse-effect level (NOAEL) values for 14, 28, and 42 days during weaning, on changes in the parameters of the oxidoreductive balance, cytokine secretion, and basal metabolism in ileal Payer’s patches. Immunoenzymatic ELISA tests and biochemical methods were used to measure the concentrations of interleukin 1α, interleukin 1β, interleukin 12/23p4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
(73 reference statements)
1
8
0
Order By: Relevance
“…However, the NF-κB pathway is a potential pathogenic factor which, when activated incorrectly or in excessive amounts, exerts adverse effects on cells. Obremski et al [ 9 ] arrived at similar conclusions in a study investigating the effects of very low ZEN doses on (i) the secretion of proinflammatory cytokines, (ii) the secretion of anti-inflammatory and regulatory cytokines, (iii) oxidative stress markers, and (iv) basic metabolic markers. They found that low ZEN doses induced an inflammatory response.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…However, the NF-κB pathway is a potential pathogenic factor which, when activated incorrectly or in excessive amounts, exerts adverse effects on cells. Obremski et al [ 9 ] arrived at similar conclusions in a study investigating the effects of very low ZEN doses on (i) the secretion of proinflammatory cytokines, (ii) the secretion of anti-inflammatory and regulatory cytokines, (iii) oxidative stress markers, and (iv) basic metabolic markers. They found that low ZEN doses induced an inflammatory response.…”
mentioning
confidence: 66%
“…At present, risk evaluations focus mainly on mycotoxins’ ability to modify the metabolic profile and their proinflammatory, mutagenic, cytotoxic, and potential carcinogenic effects [ 6 , 7 , 8 , 9 ]. Rykaczewska et al [ 6 ] reported that pre-pubertal gilts responded differently to ZEN administered at the lowest-observed-adverse-effect level (LOAEL), no-observed-adverse-effect level (NOAEL), and minimal anticipated biological effect level (MABEL) doses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, we measured key immune genes including pro-inflammatory factors (IL-1β, IL-6, TNFα), anti-inflammatory factors (IL-10, TGFβ1), and genes related to inflammation and apoptosis (TLR3, TLR22, Myd88, IκBα, P65, Bcl-2, Bax, Casp3, Casp8, and Casp9). These genes play a critical role in regulating immune responses and maintaining health in fish liver [ 46 , 56 ], involving various immune pathways such as anti-inflammatory reactions and apoptosis, and are important indicators of fish immune health [ 57 ]. Our results revealed significant changes in the expression of liver immune genes in the hybrid group under different probiotic treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal dysfunctions can lead to serious diseases and disorders that impair bodily functions. Endocrine disorders can be caused by numerous factors [ 10 ], including undesirable substances such as EDCs, e.g., ZEN [ 11 , 12 , 13 , 14 , 15 ]. These compounds disrupt various processes in the endocrine system, including biosynthesis, transport, metabolism, receptor and post-receptor expression, and feedback mechanisms.…”
Section: Introductionmentioning
confidence: 99%